A tailored biocatalyst achieved by the rational anchoring of imidazole groups on a natural polymer: furnishing a potential artificial nuclease by sustainable materials engineering. Issue 28 (10th March 2015) - Ferreira, José G. L.; Grein-Iankovski, Aline; Oliveira, Marco A. S.; Simas-Tosin, Fernanda F.; Riegel-Vidotti, Izabel C.; Orth, Elisa S.
Abstract : Biocatalysts were obtained by anchoring imidazole groups on the biocompatible gum arabic, with catalytic activity in dephosphorylation reactions and cleavage of plasmid DNA. Abstract : Foreseeing the development of artificial enzymes by sustainable materials engineering, we rationally anchored reactive imidazole groups on gum arabic, a natural biocompatible polymer. The tailored biocatalyst GAIMZ demonstrated catalytic activity (>10 5 -fold) in dephosphorylation reactions with recyclable features and was effective in cleaving plasmid DNA, comprising a potential artificial nuclease.